Effect of high O2 treatments on physiochemical, lycopene and microstructural characteristics of cherry tomatoes during storage. Issue 11 (3rd October 2019) - Guo, Yanli; Jiang, Jianan; Pan, Yanfang; Yang, Xiaoyu; Li, Haideng; Li, Hui; Xu, Mengjun; Li, Xihong
Abstract: In order to study the resistance of microstructural characteristics and the changes of physical and chemical indexes in cherry tomatoes during its storage period, fresh cherry tomatoes were treated with high O2 (40%, 60%, 80%, and 100%). The results showed that pure oxygen treatment inhibited the decay rate of tomato significantly, delayed the improvement of membrane permeability, reduced lipid peroxide content, and maintained a good cell structure. Compared with the control, the tomato with 100% oxygen concentration treatment obtained the best results after 28 days of storage, which reflected in that the decay rate is only 30%, titrable acidity (TA) decreased by 53%, malondialdehyde (MDA) was 3.8 mmol/kg and lycopene was 3.1 mg/100 g, and smallest increase of electrical conductivity from 24% to 45%. High concentration oxygen could avoid the anaerobic respiration of tomato to some extent and reduce the production and accumulation of acetaldehyde, ethanol, and ethyl acetate. Practical applications: High oxygen (21%–100% O2 ) processing technology, developed in recent years, is one of the postharvest processing techniques of fruit and vegetables. Metabolism of cherry tomatoes after picking was deeply modified by the application of high oxygen, which inhibited the decay and delayed the ripening. Cherry tomatoes exposed to high oxygen concentration (100% O2 ) were shown to have a lower increase in relative electrolyte leakage rate and lipid peroxidation as well as lower membrane damage. High O2 treatment technology is expected to develop into a new concept of controlled atmosphere storage technology, which will play a significant role in fruit and vegetables in storage.